2019
DOI: 10.21037/atm.2019.01.35
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of intraoperative re-dose of prophylactic antibiotics on surgical site infection in diabetic patients: a retrospective cohort study

Abstract: Background: Surgical site infection (SSI) has a high incidence in diabetic surgical patients. Preoperative antibiotic prophylaxis followed by an intraoperative re-dose was a common strategy in diabetic prolonged procedures. However, there were lacking studies on the relative benefits of this strategy on SSI. Our study aimed to clarify the effect of intraoperative re-dose of prophylactic antibiotics on SSI in diabetic patients. Methods: A total of 1,840 diabetic patients with prolonged surgeries were included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…20 Study in Italy found only moderate compliance with this recommendation. 21 Whereas 86% adherence to timing of administration prior to incision was noted in study of Berrondo et al 22 SAP was administered 90 min in Bertschi D et al23, De Jong et al 24 study, and was administered 60 minutes before surgery in Kasatpibal et al 25 and Zhang X et al 26 study, In our study non-compliance in pre-op dose timing was seen in only one unit, that was due to some administrative issues and was later on resolved.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…20 Study in Italy found only moderate compliance with this recommendation. 21 Whereas 86% adherence to timing of administration prior to incision was noted in study of Berrondo et al 22 SAP was administered 90 min in Bertschi D et al23, De Jong et al 24 study, and was administered 60 minutes before surgery in Kasatpibal et al 25 and Zhang X et al 26 study, In our study non-compliance in pre-op dose timing was seen in only one unit, that was due to some administrative issues and was later on resolved.…”
Section: Discussionmentioning
confidence: 98%
“…Poor adherence to antibiotic prophylaxis recommendations has been shown in other studies with similar results. 26,27 We tried to evaluate the reasons for non-compliance and it was noted that knowledge gaps, overcautious attitude of the surgeons, fear of losing faith by the patients, and non-availability of the desired drug in the hospital inventory were few of the reasons for the same. One of the most critical reasons noted was the lack of local evidence from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is suggested that bowel cleansing can be safely omitted in colonic surgery without inducing a higher complication rate. However, results from other studies suggest that the use of MOABP is associated with more favorable outcomes (30)(31)(32)(33)(34). The largest study involves three large retrospective cohort studies of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP), targeting colectomy data (32,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still problems with the aforementioned treatments. For those patients whose condition is not improved by oral medication, bariatric surgery can only be used in a small number of people [9][10][11], and interventional administration of insulin injection also brings endless torment. Reverse-engineer would replace the surgery to nd less invasive and more equivalent therapeutics.…”
Section: Introductionmentioning
confidence: 99%